The Role of the Tarteel Application in Maintaining the Memorization of Al-Qur'an Memorizers - Naufal, Ahmad Ghani; Dahliana, Yeti; Prasetyo, Arif (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
The Quran is considered the word of Allah and was revealed to the last messenger by the angel Gabriel. It is a religious duty for Muslims to read the Quran, as they believe it to be the only reliable source of life guidance. The Prophet Muhammad SAW was instructed to have specialists write down the verses whenever they were revealed, ensuring that the Quran was constantly maintained. Memorizing the Quran is considered one of the greatest virtues and the highest form of worship before Allah SWT. There are various techniques for memorizing the Quran, including the Sorongan method, which has drawbacks such as lower time efficiency and effectiveness, as well as difficulties with memorization, including boredom and forgetfulness. To make memorizing the Quran easier and more effective, an application has been developed, providing personalized and interactive features tailored to individual needs. Additionally, the application addresses the monotony of the memorization process and can improve concentration and memory quality. The innovative Tarteel AI technology combines artificial intelligence to make learning the Quran more organized and effective. The application offers benefits such as reciting, memorizing, and searching the Quran. This study employs a descriptive qualitative literature research methodology and uses data reduction, data presentation, and data analysis techniques to acquire reliable data.   Keywords: Application, Tarteel, Memorizing, Al-Qur'an